Pendidikan Islam Masa Dinasti Abbasiyah dan Perkembangan Pendidikan Islam Masa Modern - Wira Kurnia Listari; Alimni Alimni (Yayasan Darussalam Bengkulu, 2025)
Education is a place where the teaching and learning process takes place through interaction with the surrounding environment. Islamic educational institutions strive to enhance students' faith, understanding, appreciation, and experience of Islam, thus becoming faithful and pious individuals in their personal, social, national, and state lives. Islamic education began to develop during the time of the Prophet Muhammad (peace be upon him), the Caliphate of the Righteous, the Umayyad, and the Abbasids, and continues to develop to this day. Islamic education progressed especially during the Abbasid Dynasty. This article aims to discuss the concept of Islamic education during the Abbasid dynasty and the development of modern Islam. This research method uses a descriptive qualitative approach. Information sources for this study were obtained from various sources, including print and online media related to the topic. The results of this article, based on the form and nature of Islamic educational institutions during the Abbasid dynasty, can be categorized into three types: informal educational institutions, such as the homes of scholars; non-formal educational institutions, such as kutabs, mosques, bookstores, and libraries; and formal educational institutions, such as madrasas. The sheer number of educational institutions demonstrates that this aligns with the Islamic belief that seeking knowledge is obligatory and considered an act of worship. Therefore, places of learning are diverse, not concentrated in a specific location.